Contrasting association of circulating sCD14 with insulin sensitivity in non‐obese and morbidly obese subjects. Issue 1 (20th July 2015) - de Courten, Barbora; Moreno‐Navarrete, José Maria; Lyons, Jasmine; Soldatos, Georgia; de Courten, Maximilian; Dougherty, Sonia; Forbes, Josephine; Fernández‐Real, José Manuel
Abstract : Scope: In experimental studies, moderate to high concentrations of sCD14 (serum cluster of differentiation 14 protein) prevent lipopolysaccharide (LPS)‐induced systemic inflammation, while low concentrations may promote inflammation. Given that metabolic endotoxemia is thought to initiate high‐fat diet‐induced insulin resistance, we explored the association between sCD14 concentrations and insulin sensitivity in humans. Methods and results: Healthy non‐obese ( n = 12, BMI 26 ± 5y), obese ( n = 11, BMI 33.45 ± 3.2) and morbidly obese participants ( n = 38, BMI 45 ± 7) underwent measurement of body composition (dual energy X‐ray absorptiometry) and a hyperinsulinemic‐euglycemic clamp to measure insulin sensitivity (M value). Circulating sCD14 concentrations were measured by ELISA. Non‐obese participants had lower circulating sCD14 concentrations compared to obese ( p = 0.03). Circulating sCD14 concentrations were positively associated with percent body fat, waist circumference and white blood cell count and negatively associated with insulin sensitivity. In contrast, circulating sCD14 were positively associated with insulin sensitivity in morbidly obese participants. In regression analysis, insulin sensitivity ( r = 0.52, p = 0.004) and fasting triglycerides ( r = 0.49, p = 0.005) contributed independently to circulating sCD14 variance after controlling for age, sex and BMI in these morbidly obese subjects. Conclusion: These findings suggest that circulating sCD14 concentrations, through its compensatory (in non‐obese subjects) or buffering role (in morbidly obese subjects), could exert an important role in modulating insulin sensitivity.